Uterine Niche: A Pathology to Consider - Mendes,Francisca (2024)
Abstract Uterine niche is a recess located in the anterior wall of the uterine isthmus, over the cesarean section scar. This condition is often asymptomatic, but it can be associated with symptoms such as abnormal uterine bleeding, pelvic pain and secondary infertility. Endovaginal ultrasound is the first-line diagnostic method. Treatment includes hormonal methods or surgery, and surgical treatment seems to be the most effective in resolving symptoms. We describe the case of a 37-year-old woman, with an obstetric history of a pregnancy with cesarean delivery, who complained of pelvic pain and menstrual irregularity. An endovaginal ultrasound was requested, which reported the presence of a “… echogenic oval formation with well-defined limits measuring 28x17 mm in the topography of the cesarean scar.” After a clinical discussion with a doctor specializing in Gynecology, the patient was referred to a hospital consultation in this specialty for investigation. The diagnosis of uterine niche was confirmed, and the treatment consisted of the placement of an intrauterine system.